Study on nanostructured zinc oxide thin films characteristics - Mohd Rodzi, Ana Syahidah (2014)
The Nano structured zinc oxide (ZnO) materials in thin film have been achieved using electrochemical deposition (ECD) method. The morphology, crystal structure and optical properties of ZnO nanostructures have been characterized. The best potentials for deposition were -1.0V and -1.1V using ECD method. Analysis using (FESEM) showed that ZnO nanoparticles and nanorods growths uniformly. The XRD patterns of ZnO nanostructure thin films shows evident in good arrangement of crystal structure properties that has been investigated in high deposited temperature at 95 °C and annealed at 500 °C. It is proved that ZnO thin film texture surface with the c-axis perpendicular to the substrate surface. Deposition of ZnO seed catalysis growth of hexagonal wurtzite structure of ZnO and exhibited good arrangement of ZnO nanorods growth investigated at -1.0V, -1.1V, -1.2V, 1.3 V and -1.4V of the potential applied. The highest transmittance spectra of -1.0V potential applied showed 80% transmittance spectra compared to that of other potentials which deposited at high deposition temperature. F or piezoelectric properties, results at -1.0 V, -1.1 V and -1.2 V of ZnO thin films can give signal corresponding to the average of current output600 nA, 200 |iA and 50 |iA, respectively. As a conclusion, the excellent ZnO nanostructures properties growth by ECD method has been achieved for the best deposition potential at -1.0 V and -1.1 V. Otherwise to improve the crystallites of ZnO has been prepared at high temperature deposition 95 °C compare low temperature deposition. The high percentage transmittance has been exhibited at 80% after annealed in oxygen furnace to improve the optical properties.